PENINGKATAN PERAN TEKNOLOGI DALAM PENGELOLAAN DATA PESERTA DIDIK YANG BELUM BISA DIAKSES OLEH SELURUH PIHAK SEKOLAH - Hilda Handayani; Siti Nurkamilah; Ejen Jenal Mutaqin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the use of technology in student data management at SDN 1 Rancabango, which has not yet been fully mastered by all school officials. Technological developments have a significant impact on student data management because they enable more efficient, accurate, and integrated processes and support data-driven decision-making to improve the quality of education. However, the implementation of technology in data management still faces various challenges, such as limited infrastructure, low competency of educators in utilizing technology, and issues of data security and privacy. This study used a qualitative method with a descriptive research type. Data were obtained through observation, interviews, and documentation. The results show that optimizing technology utilization can be achieved through strengthening technological infrastructure, improving human resource competency through training, good data security management, and collaboration with the government and related parties. In addition, regular evaluation and feedback from technology users are also needed to ensure the effectiveness and sustainability of the system used. With a comprehensive approach and cooperation from all parties, the use of technology is expected to increase the effectiveness of student data management and support improvements in the quality of education. Therefore, it is recommended that schools continue to improve human resource competencies, strengthen technological infrastructure, and develop secure and integrated data management systems to support more effective and sustainable student data management.